The relationship of laboratory values with prognosis in acute stroke recanalization treatment applied patients - Acır, İbrahim and Erdoğan, Hacı Ali and Olgun Yazar, Hülya and Suskun, Melis and Yayla, Vildan (The European Research Journal, 2023)
Objectives: Many factors affect the results of acute recanalization treatment and prognosis of ischemic stroke patients. Some markers which has a role in inflammation process cause atherosclerosis that leads to ischemic stroke. We aimed to evaluate the relationship between admission laboratory findings and prognosis in patients to whom acute recanalization therapy were applied. Methods: In our study, we evaluated 139 acute stroke patients to whom acute recanalization therapies had been applied. Demographic data, glomerular filtration rate, uric acid, albumin, lipid profile, C-reactive protein, fibrinogen values were evaluated. Admission and discharge National Institutes of Health Stroke Scale and modified Rankin Scale scores were recorded. The effect of laboratory parameters on prognosis was examined. P <0.05 was considered significant. Results: Tissue plasminogen activator therapy was applied to 53 (38.1%) patients, thrombectomy to 62 (44.6%) patients, tPA bolus+thrombectomy to 3 (2.2%) patients, tPA full dose+thrombectomy to 19 (13.7%), and thrombectomy+stent to 2 (1.4%) patients. None of the laboratory were statistically related to prognosis except for lymphocytes count (p = 0.012) and albumin (p = 0.01). There was no relationship between laboratory findings with hemorrhagic transformation and acute recanalization treatment outcome. Conclusions: In the etiology of ischemic stroke, there are many inflammatory processes that cause atherosclerosis such as hypertension, hyperlipidemia, diabetes mellitus. The effect of admission laboratory values on prognosis has not been clarified. In patients with acute recanalization therapies, admission laboratory findings has no effect on patient management. Consequently, laboratory parameters provide limited information about the prognosis of patients who underwent acute recanalization therapies.